Casablanca - Alison, Joan; Bergman, Ingrid, 1915-1982; Bogart, Humphrey, 1899-1957; Burnett, Murray; Curtiz, Michael, 1888-1962; Edeson, Arthur, 1891-1970; Epstein, Julius J., 1909-2000; Epstein, Philip G.; Greenstreet, Sydney; Henreid, Paul; Koch, Howard; Lorre, Peter; et al. (Warner Home Video, 2003)
Set in World War II Morocco within a city filled with European refugees. A bitter nightclub owner helps his former lover and her Resistance-hero husband escape from the Nazis.